الطلاق العاطفي في ضوء بعض المتغيرات لدى الطلبة المتزوجين في جامعة بغداد - ابراهيم خليل العبيدي, عفراء (University of Eloued جامعة الوادي, 2015)
هدف البحث الحالي التعرف على الطلاق العاطفي لدى طلبة الجامعة المتزوجون فضلا عن التعرف على الفروق في الطلاق العاطفي لدى الطلبة وفق متغير الجنس (ذكور – اناث) وكذلك وفق متغير مدة الزواج والحالة الاقتصادية والفارق العمري بين الزوجين ، تكونت عينة البحث من (150) طالباً وطالبة ( من الطلبة المتزوجون)، وبعد تطبيق مقياس البحث وتحليل الاجابات كشفت نتائج البحث ان طلبة الجامعة يعانون من الطلاق العاطفي، وكذلك بينت النتائج وجود فروق في الطلاق العاطفي وفق متغير مدة الزواج ولصالح (اقل من 5 سنوات) والحالة الاقتصادية ولصالح الحالة الاقتصادية غير الجيدة والفارق العمري ولصالح الفارق العمري ( اكثر من 5 سنوات) بينما لم تظهر النتائج وجود فروق في الطلاق العاطفي بين الجنسين Emotional divorce in light of some variables among married students at the University of Baghdad Abstract The goal of current research to identify the emotional divorce among university students married couples as well as to identify the differences in emotional divorce among students according to variable sex (males - females) as well as in accordance with the duration of marriage variable economic situation and the age gap between the couple, formed the research sample of (150) students (of married students)After applying scale research and analysis of the answers revealed the search results that college students suffering from emotional divorce) As well as the results showed the existence of differences in the emotional divorce in accordance with the variable duration of marriage and in favor of (less than 5 years) and the economic situation and in favor of the economic situation is good and the age gap and for the age gap of more than 5 years), while the results did not show the existence of differences in the emotional divorce between the sexes.
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: الطلاق العاطفي